Istota raportowania społecznego. Budowanie wartości czy instytucjonalny przymus? = The essence of social reporting. Value building or institutional coercion? - Nieporowski, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to objectively discuss the sense and values stemming from the examination and reporting by companies about their socio-ecological engagement under the Corporate Social Responsibility (CSR) concept. The author refers to the publications and research reports describing extra-financial reporting prepared by companies in Poland, and to his own analysis of periodical social reports published by companies and of the content of their websites.
Keywords: raportowanie pozafinansowe; ESG; społeczna odpowiedzialność biznesu; CSR; extra-financial reporting; corporate social responsibility